Perception of Dora Pejačević in Croatian Public Printed Media from 1905 to 1945 - Stanislav Tuksar (Arti Musices)
The perception of the female composer Dora Pejačević in the Croatian public media (newspapers and magazines) in the period from 1905 to 1945 can be traced through about fifty articles. Reports and comments on her character and work were published by a total of 24 newspapers, mostly in Zagreb and Osijek, and in addition to twelve anonymous authors and six signed only with initials, 18 authors were identified for 25 of these articles. The main part of this text consists of citing and analyzing the writings of the six most important authors who wrote about D. Pejačević in the mentioned period: Ern(e)st Schulz, Milutin Nehajev, Viktor Novak, Petar Konjović, Božidar Širola and Lujo Šafranek-Kavić. The writings of these six authors were singled out because of their opinion and evaluation of the life and work of D. Pejačević at a level higher than usual newspaper reports, as creators of perception and not as mere chroniclers of reception, and because of the reputation they enjoyed among the public in their time as critics, composers and musicologists. These writings show a considerable diversity in the approach and evaluations of both individual works and the entire musical habitus of D. Pejačević.